2022
DOI: 10.3390/ijms23158365
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Comparison of the DPP-IV Inhibitory Potential of Food Proteins from Different Origins after Gastrointestinal Digestion

Abstract: Dipeptidyl-peptidase IV (DPP-IV) plays an essential role in glucose metabolism by inactivating incretins. In this context, food-protein-derived DPP-IV inhibitors are promising glycemic regulators which may act by preventing the onset of type 2 diabetes in personalized nutrition. In this study, the DPP-IV-inhibitory potential of seven proteins from diverse origins was compared for the first time in vitro and in vivo in rat plasma after the intestinal barrier (IB) passage of the indigested proteins. The DPP-IV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
1
12
2
Order By: Relevance
“…dWPH decreases TEER and increases apparent permeability after 2 hours of incubation at a concentration of 31.25 mg.mL -1 but has no effect at 10 mg.mL -1 (Figure 3B and 3C). This is in agreement with our already published result which showed that a digested whey protein isolate decreased the TEER of Caco-2/HT-29MTX monolayer (29). The apparent permeability coefficient calculated with 31.25 mg.mL -1 of dWPH remained however acceptable (9,2.10 -7 ± 6,2.10 -7 cm.s -1 ).…”
Section: Food and Function Accepted Manuscriptsupporting
confidence: 92%
See 2 more Smart Citations
“…dWPH decreases TEER and increases apparent permeability after 2 hours of incubation at a concentration of 31.25 mg.mL -1 but has no effect at 10 mg.mL -1 (Figure 3B and 3C). This is in agreement with our already published result which showed that a digested whey protein isolate decreased the TEER of Caco-2/HT-29MTX monolayer (29). The apparent permeability coefficient calculated with 31.25 mg.mL -1 of dWPH remained however acceptable (9,2.10 -7 ± 6,2.10 -7 cm.s -1 ).…”
Section: Food and Function Accepted Manuscriptsupporting
confidence: 92%
“…Recently, we showed that the origin of the proteins led to different gastrointestinal-resistant peptidomes notably as a result of their native sequence, their digestibility and their conformation. These differences impacted the inhibitory potential of the DPP-IV activity, in vitro and in situ at the intestinal level but also in vivo in rat plasma (29). In contrast, in the present study, pre-hydrolysis of whey proteins did not modify the DPP-IV activity inhibitory effect in vitro and in situ at the intestinal level before the passage of the intestinal barrier.…”
Section: Food and Function Accepted Manuscriptcontrasting
confidence: 92%
See 1 more Smart Citation
“…• It's not causing the weight gain or hypoglycemia [53] • Maybe have drug interaction risk [53] PTP-1B inhibition…”
Section: Assaymentioning
confidence: 99%
“…Dietary proteins can be an excellent source of bioactive peptides, with several biological activities. Fleury et al [ 7 ] investigated the ability of some dietary proteins and the peptides derived from their in vitro digestion to inhibit the activity of the enzyme dipeptidyl-peptidase IV (DPP-IV). This enzyme is a pharmacological target in type-2 diabetes therapy since it is involved in the degradation of the insulinotropic incretin hormones.…”
mentioning
confidence: 99%